Air temperature and water level inferences from northeastern Lapland (69 degrees N) since the Little Ice Age - Luoto, Tomi P.; Kivila, E. Henriikka; Kotrys, Bartosz; Plociennik, Mateusz; Rantala, Marttiina; Nevalainen, Liisa (Polish Academy of Sciences. Committee on Polar Research, 2020)
Independent Arctic records of temperature and precipitation from the same proxy archives are rare. Nevertheless, they are important for providing detailed information on long-term climate changes and temperature-precipitation relationships in the context of large-scale atmospheric dynamics. Here, we used chironomid and cladoceran fossil assemblages to reconstruct summer air-temperature and water-level changes, during the past 400 years, in a small lake located in Finnish Lapland. Temperatures remained persistently cold over the Little Ice Age (LIA), but increased in the 20th century. After a cooler phase in the 1970s, the climate rapidly warmed to the record-high temperatures of the most recent decades. The lake-level reconstruction suggested persistently wet conditions for the LIA, followed by a dry period between similar to 1910 and 1970 CE, when the lake apparently became almost dry. Since the 1980s, the lake level has returned to a similar position as during the IAA. The temperature development was consistent with earlier records, but a significant local feature was found in the lake-level reconstruction the LIA appears to have been continuously wet, without the generally depicted dry phase during the 18th and 19th centuries. Therefore, the results suggest local precipitation patterns and enforce the concept of spatially divergent LIA conditions. Peer reviewed